2023
DOI: 10.1111/liv.15663
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use and development of nonalcoholic fatty liver disease: A population‐based case–control study

Abstract: Background and AimsAntibiotics affect the gut microbiome. Preclinical studies suggest a role of gut dysbiosis in the development of nonalcoholic fatty liver disease (NAFLD), but data from large cohorts with liver histology are lacking.MethodsIn this nationwide case–control study, Swedish adults with histologically confirmed early‐stage NAFLD (total n = 2584; simple steatosis n = 1435; steatohepatitis (NASH) n = 383; non‐cirrhotic fibrosis n = 766) diagnosed January 2007–April 2017 were included and matched to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…An-tibiotic use was found to be a risk factor for incident NAFLD, especially in individuals without metabolic syndrome. The risk was very significant for fluoroquinolones and remained robust in sibling comparisons with whom individuals shared genetic and early environmental susceptibilities [60].…”
Section: The Link Between Antibiotics and Nafldmentioning
confidence: 92%
“…An-tibiotic use was found to be a risk factor for incident NAFLD, especially in individuals without metabolic syndrome. The risk was very significant for fluoroquinolones and remained robust in sibling comparisons with whom individuals shared genetic and early environmental susceptibilities [60].…”
Section: The Link Between Antibiotics and Nafldmentioning
confidence: 92%
“…Consequently, many countries have restricted or prohibited the use of antibiotics as growth promoters in livestock [4,5]. Furthermore, recent Animals 2024, 14, 1057. https://doi.org/10.3390/ani14071057 https://www.mdpi.com/journal/animals clinical and rodent research has suggested a potential link between antibiotics and obesityrelated metabolic disorders, with specific antibiotics implicated in gut microbiota changes and lipid ectopic deposition [6][7][8][9][10]. The altered gut microbiota has been reported to play a key role in host metabolism, as indicated by the ability to replicate metabolic disorders in germ-free recipients inoculated with penicillin-altered bacteria [11].…”
Section: Introductionmentioning
confidence: 99%